Soliciting and providing online social support in the self-disclosure of eating disorders / Nur Azwin Zulkarnain - Nur Azwin , Zulkarnain (2019)
Eating disorders (ED) are considered as one of the mental health problems that require much attention and support. The present study focuses on the online construction of selfdisclosure of individuals suffering from ED and demonstrate how strategies of soliciting and providing online social support, as well as their level of directness are mediated within the public sphere. The participations of individuals with ED in online support groups are more preferred due to it being more accessible and non-costly compared to offline settings (McCormack, 2010). Even so, Basile (2004) argued how not many of them have the courage to disclose about their illness and prefer secrecy. This serves as motivation for data to be collected from one of the discussion forums on the National Eating Disorders Association (NEDA) website, the Working Toward Recovery forum. A total of 113 relevant posts of self-disclosure containing instances of online solicitation and provision of support dated from January 2018 to March 2018 are analyzed using the computer-mediated discourse analysis method. As for the frameworks of the study, North’s (1997) Strategies of Soliciting Social Support, Cross-Cultural Study of Speech Act Realization Patterns (CCSARP) by Blum-Kulka and Olshtain (1984), and McCormack’s (2010) Categories of Social Support are adopted. The findings have shown consistent result with past studies where sharing of experience is regarded as the most frequent strategy of soliciting support opted by online support-seekers, while having to show appreciation appears to be the least. Most posts that consist of shared experience are comparably lengthier than those that do not as they usually involve detailed explanation of the individuals’ problems. With regards to providing social support, almost half of the strategies were found to be in the form of encouragements, followed by providing personal opinions as the second most utilized. Further, encouragement and esteem were inferred to be primarily used as a source of mitigation and followed by other strategies that could have the possibility of impositions. In addition, the findings also revealed a common pattern of directness in the acts of soliciting and providing support. Even via a direct solicitation of support, it would commonly result with the support being provided indirectly, and occasionally a more direct one. However, an indirect supportsolicitation would also lead to support-providers being indirect with their manners of supporting as well and they are rarely direct. Thus, believing that support-providers prefer to approach ED patients indirectly as a way to cushion their manners of supporting rather than being completely explicit in terms of language used. Despite the ability of being anonymous in an online setting, support-providers have shown a positive attitude in assuring that the social support acquired by ED patients is delivered in a way that it can be regarded as acceptable, appropriate and not imposing. Even when the support attained in the NEDA forum is presumed to be willingly solicited by ED patients as their participation in the forum is based on their own intuition, maximum acceptance of the support is still a priority to those who provide it.